Influential factors of online scam awareness among generation X in Malaysia - Quek, Hui Ling (2023)
This research investigates the influential factors shaping online scam awareness among Generation X in Malaysia. Through a comprehensive analysis of key variables – risk perception, skepticism, media exposure, security concerns, and social support, the study explores their relationships and implications for scam awareness in the digital landscape.